2020
DOI: 10.3389/fpls.2020.01118
|View full text |Cite
|
Sign up to set email alerts
|

Cysteine and Methionine Biosynthetic Enzymes Have Distinct Effects on Seed Nutritional Quality and on Molecular Phenotypes Associated With Accumulation of a Methionine-Rich Seed Storage Protein in Rice

Abstract: further improve the methionine content in rice should focus on increasing seed sulfur loading and avoiding the accumulation of unfolded proteins in the endoplasmic reticulum.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 80 publications
(143 reference statements)
0
3
0
Order By: Relevance
“…Indeed, metabolism is shaped by genes, but metabolic machinery is affected by changes in the concentration of metabolites, which, in turn, can act as substrates and cofactors for post-translational modifications. Although recognized, this fact could be exemplified with the pool of methyl donor S-methyl methionine (SMM) and S-adenosyl methionine (SAM), synthetized from methionine, as SAM/SMM can fluctuate in concentration, limit activity of methyltransferases, and influence regulation of gene expression in several organisms [ 19 , 20 ]. Our results open a door to study whether genes in charge of transport and assimilation can be regulated by a pool of sulfur organic compounds in algae.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, metabolism is shaped by genes, but metabolic machinery is affected by changes in the concentration of metabolites, which, in turn, can act as substrates and cofactors for post-translational modifications. Although recognized, this fact could be exemplified with the pool of methyl donor S-methyl methionine (SMM) and S-adenosyl methionine (SAM), synthetized from methionine, as SAM/SMM can fluctuate in concentration, limit activity of methyltransferases, and influence regulation of gene expression in several organisms [ 19 , 20 ]. Our results open a door to study whether genes in charge of transport and assimilation can be regulated by a pool of sulfur organic compounds in algae.…”
Section: Discussionmentioning
confidence: 99%
“…Cysteine is a component of wheat gluten. It was reported that increasing the cysteine content in the cereal kernels, increasing its quality (Whitcomb et al 2020). Therefore, this network is very important in improving wheat tolerance to Pb as well as producing kernel yield with high end-use quality.…”
Section: Gene Enrichment Biological Processes and Network Of Genes Co...mentioning
confidence: 99%
“…Altering feedback inhibition. Many enzymes at the head of pathways are inhibited by downstream pathway intermediates or end-products and relieving this feedback inhibition is often effective in increasing flux in such pathways [51,52]. Selecting for feedback-insensitive microbial enzymes has a long track record of success [53][54][55] and can be extended to plant enzymes in microbes engineered to express them [56,57].…”
Section: Future Perspectivesmentioning
confidence: 99%